Black African philosophy denied. Hermeneutic rationality aborted - (:unkn) unknown (My University, 2025)
This article aims to provide an account of Basile-Juléat Fouda's philosophical work, which is characterised as a Black African existential philosophy, pejoratively labelled as ethnophilosophy. Indeed, while Fouda sought to grasp culture from the ordinary life of Black Africans through a liberation of its interpretive possibility, his philosophical effort, whose essential material was African oral literature, met a singular fate in the African philosophical debate due to the exclusive adherence to Eurocentric critical thinking. However, the typical case of a comprehensive approach to his object, that of a hermeneutic of human and universal meaning, was doubly rejected: first, as reactionary - simply because it was developed in the wake of the affirmation of the existence of an original African philosophy; and secondly, because it was perceived as a revision of the very notion of philosophy, in the sense of an enlargement that would lead to a proper understanding of African modes of thought. Since it was a completely different orientation, it was considered a dilution of philosophy into culture for the purpose of demonstrating the existence of a Black African philosophy. However, the Black African philosophy thus denied only paid the price of methodological dissidence. For we see in it the preludes of a clash of approaches on African philosophical soil, concurrent with that of Gadamer and Habermas on European philosophical soil, between 'interpretive reason' and 'critical reason' known and recognized until then.
Keywords: African Research